2014
DOI: 10.1038/srep07128
|View full text |Cite
|
Sign up to set email alerts
|

Low Piconewton Towing of CNS Axons against Diffusing and Surface-Bound Repellents Requires the Inhibition of Motor Protein-Associated Pathways

Abstract: Growth cones, dynamic structures at axon tips, integrate chemical and physical stimuli and translate them into coordinated axon behaviour, e.g., elongation or turning. External force application to growth cones directs and enhances axon elongation in vitro; however, direct mechanical stimulation is rarely combined with chemotactic stimulation. We describe a microfluidic device that exposes isolated cortical axons to gradients of diffusing and substrate-bound molecules, and permits the simultaneous application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 58 publications
(100 reference statements)
0
46
0
3
Order By: Relevance
“…(ii) Does soma-axon communication coordinate axonal Netrin-1 response? The former question can be addressed with different microfluidic designs involving concentration gradients that are parallel 56 or orthogonal 33 to the direction of initial axonal growth. The latter question can be addressed by using the circuit design presented in this study by treating fluidically-isolated somata and subsequently observing axon behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) Does soma-axon communication coordinate axonal Netrin-1 response? The former question can be addressed with different microfluidic designs involving concentration gradients that are parallel 56 or orthogonal 33 to the direction of initial axonal growth. The latter question can be addressed by using the circuit design presented in this study by treating fluidically-isolated somata and subsequently observing axon behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse cortical neurons were obtained from embryonic day 14 CD-1 outbred mouse and dissociated according to established protocols. 56 Neurons were seeded in the somatic chamber at a density of approximately 8×10 5 cells/cm 2 and maintained in a tissue culture incubator (5% CO 2 , 37°C) in DMEM-Glutamax medium containing 10% fetal bovine serum, Pen/Strep, and B 27 neuron supplement (all from Gibco, Dun Laoghaire, Ireland). At 3 DIV, the medium was replaced with Neurobasal medium (Gibco) containing Pen/Strep and B 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry in these devices followed the same protocol with minor adaptations as described previously. 30 Substrates that were bonded to microfluidic chips were also recovered and reused. Substrates were first sonicated in detergent solution for 30 min, and the chips were carefully removed by pushing from edges.…”
Section: à2mentioning
confidence: 99%
“…Finally, to test microfluidic integration with microtopography, we bonded a bicompartmental neuron culture device described. 30 The devices consist of two compartmentssomatic and axonal-interconnected by parallel microchannels that permit axonal growth. The "hexagonal pits" pattern was manually aligned with the axonal compartment during bonding such that axons emanating from the microchannels encountered an array of pits.…”
mentioning
confidence: 99%
“…4C). 114 The inhibition of kinesin-5 motor promoted axonal towing on surfaces coated with axon repellents, suggesting the possibility of using mechano-chemical stimulation for nerve repair such as in a glia scar environment that overexpresses axonal repellents. 115 Gu and colleagues integrated nano-pumps into microfluidic culture to create cross-flows and found that the direction of fluid flow could influence axonal migration and cause axonal turning with an angle more than 90 o (Fig.…”
Section: Micro-technologiesmentioning
confidence: 99%